Injury Surveillance and Evaluation of Medical Services Utilized During the 2016 Track and Field Olympic Trials. Issue 12 (24th December 2018) - Bigouette, John Paul; Owen, Erin C.; Greenleaf, Jonathan; James, Stanley L.; Strasser, Nicholas L.
Background: Injury surveillance systems have been implemented at world championships, yet no previous work has determined the burden of injuries during the United States Track and Field Olympic Trials. Additionally, the type of medical service providers utilized throughout the meet has not been reported, leaving it unclear whether optimal staffing needs are being met. Purpose: To describe the incidence of injuries presenting to the medical team at the 2016 US Track and Field Olympic Trials (Eugene, Oregon) by event type and competitor demographics. Study Design: Descriptive epidemiology study. Methods: A retrospective review was performed of all documented injuries and treatments recorded from June 28 through July 10, 2016. Descriptive statistics and the prevalence of newly incurred injuries were calculated for registered athletes and nonathlete (ie, support) staff. The incidence of acute injuries was analyzed for registered athletes, as stratified by athlete sex and event type. Results: A total of 514 individuals were seen during the trials: 89% were athletes and 11% were supporting staff. Physicians treated 71 injuries and 14 illnesses. Of diagnosed injuries, 85% (n = 60) occurred among athletes, with hamstring strains (16.7%, n = 10) being the most prevalent. A mean of 124 medical services (median, 137; interquartile range, 65.5-179.5) were provided each day of the trials. Among medical services, 41.8% were attributed to massage therapists for athletes, while chiropractic services were the most utilized service (47.1%) by the support staff. There was an overall incidence of 59.7 injuries per 1000 registered athletes, with jumpers (109.4 per 1000) and long-distance athletes (90.4 per 1000) being the most commonly seen athletes. Conclusion: Throughout the trials, athletes participating in jumping and long-distance events were the most commonly seen by physicians, creating the potential need for an increase in staffing of physicians during meet periods when these events occur. The provided medical services appeared to follow the number of athletes competing during the trials and the need for recovery treatments after competition. Findings from this study should inform future strategy for staffing and policy development at Olympic Trials and other elite-level track and field events in the United States.